A Study of Organizational Values in Government Run Primary Health Centres in India. (June 2014) - Purohit, Bhaskar; Patel, Dharmen; Purohit, Surabhi
Background: Organizational Culture (OC) (with focus on core organizational values) has been a much neglected area for research in Government Health sector in India. The present study aimed at assessing the OC with the sole focus on the organizational values at the Government run Primary Health Centres (PHCs) in India. Methods: The study participants included 124 healthcare providers and other health staff from 24 government run PHCs in India. Instrument called OCTAPACE (Openness, Confrontation, Trust, Authenticity, Praoaction, Autonomy, Confrontation and Experimentation) was used for data collection. It consists of 40 items that measured eight different organizational values: Openness; Confrontation; Trust; Authenticity; Praoaction; Autonomy; Confrontation and Experimentation. The assessment of organizational values was based on ratings provided by respondents on the 40 items. Results: The study results indicate that Openness was the most important perceived organizational value followed by Confrontation and Trust while Autonomy and Collaboration were the least appreciated and practiced values. The study found statistically significant higher mean scores for the values of Authenticity and Collaboration for the group having more work experience. In addition, the study results also show statistically significant higher mean scores for Openness, Confrontation, Trust, Authenticity, Proactiveness and Experimentation values for paramedical and other staff in comparison to mean scores of Medical officers. Conclusion: More research is needed in the area of OC with focus on values. The overall culture in PHCs can be further improved by encouraging free sharing of ideas and expression of feelings and thoughts. More importantly, employees of health centres should be given more autonomy and freedom to take decisions in their work to improve the OC.